Assessment in vitro of brushing on dental surface roughness alteration by laser interferometry - Alessandra Miranda de Azevedo; Heitor Panzeri; Célio Jesus do Prado; José Daniel Biasoli De-Mello; Carlos José Soares; Alfredo Julio Fernandes-Neto (Sociedade Brasileira de Pesquisa Odontológica, 2008)
Noncarious cervical lesions (NCCLs) are considered to be of multifactorial origin, normally associated with inadequate brushing. This study assessed the influence in vitro of simulated brushing on NCCL formation. Fifteen human premolars were submitted to brushing in the cementoenamel junction region, using hard-, medium- and soft-bristled brushes associated with a toothpaste of medium abrasiveness under a 200 g load, at a speed of 356 rpm for 100 minutes. The surface topography of the region was analyzed before and after brushing, by means of a laser interferometer, using "cut-off" values of 0.25 and considering roughness values in mm. The initial roughness (mm) results for dentin (D / bristle consistency: 1 - soft, 2 - medium and 3 - hard) were as follows: (D1) 1.25 ± 0.45; (D2) 1.12 ± 0.44; (D3) 1.05 ± 0.41. For enamel (E / bristle consistency: 1 - soft, 2 - medium and 3 - hard), the initial results were: (E1) 1.18 ± 0.35; (E2) 1.32 ± 0.25; (E3) 1.50 ± 0.38. After brushing, the following were the values for dentin: (D1) 2.32 ± 1.99; (D2) 3.30 ± 0.96; (D3) Over 500. For enamel, the values after brushing were: (E1) 1.37 ± 0.31; (E2) 2.15 ± 0.90; (E3) 1.22 ± 0.47. Based on the results of the ANOVA and Tukey statistical analyses (a = .05) it was concluded that soft, medium and hard brushes are not capable of abrading enamel, whereas dentin showed changes in surface roughness by the action of medium- and hard-bristled brushes.